Costa Rica and Colombia in the Latin American context: Multilevel analysis of the variables associated with performance in mathematical literacy in PISA 2012 - Bartels Gómez, Sofía de los Ángeles (2016)
Tests done by the Programme for International Student Assessment (PISA) were initially directed to evaluate the education system from member countries from the Organisation for Economic Co-operation and Development (OECD). Later, other countries are incorporated, including some from Latin America, Colombia and Costa Rica among them. However, the performance of the Latin American countries is not within the limits of the PISA outstanding results. The aim of this work is to compare the variables that are related to the math academic performance according to the results launched by the PISA test in Costa Rica and Colombia. Even though both countries are different in many aspects, they are immersed in the same Latin American reality. As a consequence, a multilevel regression model of fixed and random effects is suggested because it is appropriate for this problem by including variables related to the individual and his context, getting close to the reality. As a result, it is shown that the model for both countries explains more than 57% (R-squared) of the score variability in math alphabetization. Furthermore, it is concluded that the profile of the students with the highestperformance in Costa Rica and Colombia is related to: male gender, a highest rate of coherent tenure goodswith better education opportunities, father’s higher education, a great amount of books at home, and the highestscore in the math self-sufficiency scale. Finally, an important discovery was detected since the relationship ofthe attendance preschool variable and the math alphabetization score are minimized or maximized dependingon the school the student attends.